Strategic Management of Pension Scheme in Selected Private Manufacturing Organizations in South Eastern Nigeria - Okechukwu, Elizabeth Uzoamaka; Nebo, Gerald; Eze, Jude (European Scientific Journal, ESJ, 2016)
Management of pension schemes in Nigeria has been characterized by multiple and diverse problems despite several modifications of the pension schemes by the government. The study examined the extent strategies adopted for pension management can enhance employees’ confidence in the scheme. The study adopted a survey design. The data were analyzed using tables, frequencies, and mean. Z- test was used to test the hypotheses at 0.05 significance. It was revealed that to a very large extent strategies adopted for pension and retirement management can enhance employees’ confidence in the management of the schemes. The researchers recommended among others that an efficient structural framework should be put in place always to monitor the contribution and implementation of the Contributory Pension Scheme. Pension plays an increasingly important role in the economy of any country because the money earmarked for pension could be used for the establishment of small enterprises and infrastructural development.